President Truman and the atomic bomb : opposing viewpoints - O'Neal, Michael, 1949- (Great mysteries (Saint Paul, Minn.), 1990)
Discusses the events and decisions that led to the bombing of Hiroshima in 1945, particularly Truman's role as decision maker and initiator of the act.